PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SDN 003 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Rosnihayati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low results of social studies grade II SDN 003 Pagaran Tapah Darussalam. For that research by applying the learning media. The purpose of this study was (a) to determine the ability of teachers to use the media images in the learning process; and (b) to assess student learning outcomes through the use of media images in the learning process. This study is a class action, the subjects in this study was grade II by the number of students as many as 30 people, the study was conducted in March-April 2015. In order to study this class action work well without barriers obstructing the smooth running of research, phases of action research activities classes, namely: planning / preparatory action, action, observation, and reflection. The study states that the results of social studies students has increased after application of instructional media. This is evidenced by: (a) in the first cycle of the first meeting of student activity earn a percentage 58.00%, at a meeting II increases with the percentage of 77.00%, in the second cycle student activity increased with the percentage of 83.50%, and at a meeting II increased to 88.00%; and (b) the learning outcomes of students has increased in the first cycle average student learning outcomes by 64, the second cycle increased to 65. Based on the results of this study concluded that the use of media images in improving learning outcomes second grade students in social studies in SDN 003 Pagaran Tapah Darussalam Rokan Hulu.